Pendampingan Media Sosial untuk Pemasaran UMKM Keripik Singkong Kelurahan Kuala Lahang Gaung - Juliyakta, M.Rangga; Ferliansyah; Yuliati; Khairunnisa; uswatun hasanah, Rezva; Sapi’i, M. Ilham; Abdussalam, Ridho; Fatmala Dewi, Artika; Adi Putra, Bambang Sasmita (IKHLAS: Jurnal Pengabdian Dosen dan Mahasiswa, 2025)
The production of cassava chips in Kuala Lahang Village, Gaung District, holds great potential for sustainably improving the local economy. This study analyzes the impact of cassava chip businesses on the village’s economic growth, focusing on increasing entrepreneurs’ income, creating job opportunities, and developing local community skills. This business provides opportunities for residents, especially farmers and housewives, to process local agricultural products into high-value goods with strong market demand. In addition to offering extra income, cassava chip production also opens up new job opportunities across various stages such as peeling, slicing, frying, packaging, and distribution. This initiative also fosters entrepreneurial skills at the village level. Thus, the activity not only enhances individual welfare but also contributes to strengthening the local economy and empowering the community. This analysis highlights the importance of government and stakeholder support in the form of training, access to capital, as well as adequate production and marketing facilities to maximize the economic potential of the cassava chip industry in Kuala Lahang Village